Engineering a favourable osteogenic microenvironment by heparin mediated hybrid coating assembly and rhBMP-2 loading. Issue 19 (15th February 2017) - Tan, Haoqi; Wang, Honglei; Chai, Yanjun; Yu, Yuanman; Hong, Hua; Yang, Fei; Qu, Xue; Liu, Changsheng
Abstract : (1) HApNPs are conferred with negative charges by surface modification with heparin. (2) Heparinized HApNPs and polycation CS are assembled to form a hybrid coating. (3) RhBMP-2 is introduced into the coating via the intermolecular binding with heparin. Abstract : With the development of bone tissue engineering, it is a great challenge to fabricate a bioactive surface which can provide a favourable microenvironment for cell adhesion, migration and osteo-differentiation. Coating the as-prepared substrates with bioactive components is an effective method to induce osteogenesis. In this study, we designed a multi-layered hybrid coating containing hydroxyapatite nanoparticles, heparin and chitosan. Heparin is used to mediate the electrostatic assembly of hydroxylapatite nanoparticles with chitosan, as well as the subsequent recombinant human bone morphogenetic protein-2 (rhBMP-2) loading. Several independent pieces of evidence were provided to indicate the successful fabrication of the hybrid coating. Sustained release of rhBMP-2 by this coating was also achieved. The in vitro biological studies reveal that the hybrid coating system has excellent biocompatibility and can improve the osteo-differentiation especially for rhBMP-2 present on the coating surface. The results demonstrate that the proposed rhBMP-2 loaded hybrid coating can provide a favourable osteogenic microenvironment and has the potential to improve in situ bone repair due to its superior osteoconductivity as well as osteoinductivity.